The Status of Citizens and Migrants in Light of the Non‑Discrimination Principle - Scheu, Harald Christian (Lidé města, 2014)
Migration is connected to a large number of civil and political rights like, e.g., the non-refoulement principle, the respect for private and family life, a fair trial and personal liberty, human dignity and freedom of opinion, as well as social rights like, e.g., the right to just conditions of work, the right to fair remuneration, the right to social security and the right to health care. In the international human rights doctrine there is little doubt about the close link between international protection of human rights and the regulation of migration. Also the jurisprudence of international and national courts has clearly demonstrated that migration is one of the most complex human rights issues of our time.